A heat-resistant and wear-resistant polycrystalline cubic boron nitride composite blade and a preparation method thereof

CN118204494BActive Publication Date: 2026-10-20KEENSS (SU ZHOU)PRECISION M&E EQUIP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410307882.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-18
Publication Date
2026-10-20
Estimated Expiration
2044-03-18

AI Technical Summary

Technical Problem

[0004]为了改善现有聚晶立方氮化硼刀片耐高温磨损的问题,本申请提供一种耐热磨损聚晶立方氮化硼复合刀片及制备方法

Benefits of technology

1、由于本申请通过多层结构提高刀片的硬度和抗冲击性能,通过在立方氮化硼的表面包覆一层致密的二氧化硅,能够增强复合刀片的抗冲击韧性,减少复合刀片在高温切削下硬度下降、断裂的问题。同时,通过添加有碳纳米管、碳纤维的增强层和耐磨涂层提高刀片的耐磨性能、强度和导热性能,降低切削温度,减少高温下刀片硬度下降的温度,提高复合刀片的耐高温、耐磨性能。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application relates to the technical field of metal processing tool materials, and particularly discloses a heat-resistant and wear-resistant polycrystalline cubic boron nitride composite blade and a preparation method.The heat-resistant and wear-resistant polycrystalline cubic boron nitride composite blade comprises a substrate layer, a reinforcing layer and a wear-resistant coating, the reinforcing layer is located between the substrate layer and the wear-resistant coating, the substrate layer comprises the following raw materials in parts by weight: 80-95 parts of cubic boron nitride, 10-20 parts of a metal bonding agent and 3-5 parts of an organic binder, the reinforcing layer comprises the following raw materials in parts by weight: 10-20 parts of carbon nanotubes and 5-10 parts of carbon fibers; and the cubic boron nitride is coated with a layer of nano-silicon dioxide particles on the surface.The heat-resistant and wear-resistant polycrystalline cubic boron nitride composite blade prepared by the application can improve the strength and wear resistance of the blade through the mutual cooperation of the multilayer structure, and reduce the wear phenomenon generated by cutting at high temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of metalworking tool materials technology, and more specifically, it relates to a heat-resistant and wear-resistant polycrystalline cubic boron nitride composite cutting tool and its preparation method. Background Technology

[0002] Polycrystalline cubic boron nitride (PCBN) is widely used in high-speed cutting, hard cutting, and machining of difficult-to-machine materials due to its hardness being second only to diamond and its excellent thermal stability and chemical inertness. However, with the ever-increasing performance requirements of cutting tools in modern industry, traditional PCBN inserts are no longer sufficient to meet the more demanding cutting environments.

[0003] Existing PCBN cutting tools are prone to decreased hardness and wear resistance under high temperature and high wear environments, resulting in short tool life and increased machining costs. Summary of the Invention

[0004] To improve the high-temperature wear resistance of existing polycrystalline cubic boron nitride cutting tools, this application provides a heat-resistant wear-resistant polycrystalline cubic boron nitride composite cutting tool and its preparation method.

[0005] In a first aspect, this application provides a heat-resistant and wear-resistant polycrystalline cubic boron nitride composite cutting tool, which adopts the following technical solution: A heat-resistant and wear-resistant polycrystalline cubic boron nitride composite blade includes a base layer, a reinforcing layer, and a wear-resistant coating. The reinforcing layer is located between the base layer and the wear-resistant coating. The base layer comprises the following raw materials in parts by weight: 80-95 parts cubic boron nitride, 10-20 parts binder, and 3-5 parts organic binder. The reinforcing layer comprises the following raw materials in parts by weight: 10-20 parts carbon nanotubes and 5-10 parts carbon fibers. The surface of the cubic boron nitride is coated with a layer of nano-silica particles.

[0006] By adopting the above technical solution, the composite cutting tool, made with a multi-layer structure, combines a base layer and a reinforcing layer, improving the tool's hardness, wear resistance, and impact resistance. Simultaneously, coating the surface of the composite cutting tool with a wear-resistant coating reduces wear under high-temperature environments. Furthermore, coating the surface of cubic boron nitride with a dense layer of nano-silica enhances the composite cutting tool's impact resistance and toughness, reducing the likelihood of hardness degradation and breakage during cutting.

[0007] Adding appropriate amounts of carbon nanotubes and carbon fibers can enhance the hardness, toughness, and strength of cutting tools, improve their wear resistance, and reduce breakage and damage. Simultaneously, carbon nanotubes and carbon fibers can improve the thermal conductivity of the cutting tools, effectively dissipating heat and lowering the cutting temperature, thus mitigating the problem of tool hardness degradation at high temperatures. Using organic binders combined with metal binders and cubic boron nitride improves the interfacial bonding between the metal binder and cubic boron nitride, promoting a strong bond between the organic binder, metal binder, and cubic boron nitride particles. This allows the composite cutting tool to maintain stable strength at high temperatures, reduces the shedding of cubic boron nitride particles, improves the hardness and strength of the composite cutting tool, and extends its service life.

[0008] Preferably, the carbon fibers are pre-treated with surface hybridization modification, and the surface hybridization modification method includes the following specific steps: Carbon fibers are first immersed in an acid solution for oxidation, then dried. The carbon fibers are then immersed in a mixture of concentrated hydrochloric acid and maleic anhydride, heated to react, then washed and dried. Finally, they are immersed in a urea solution and heated to react. Finally, the carbon fibers are removed, washed and dried to obtain surface-hybridized carbon fibers.

[0009] By adopting the above technical solution, the surface of carbon fiber is modified by hybridization, which can generate active oxygen-containing groups such as hydroxyl and carboxyl groups on the surface of carbon fiber. This promotes the carbon fiber to have a large specific surface area and high activation, and can be uniformly and firmly bonded to the surface of cubic boron nitride, thereby enhancing the interfacial bonding force between carbon fiber and cubic boron nitride, and thus improving the strength and impact resistance of the composite blade.

[0010] Preferably, the heating reaction temperature in the carbon fiber surface hybridization step is 60-70℃.

[0011] Preferably, the metal binder is at least two of titanium carbide, aluminum nitride, silicon nitride, and tungsten carbide.

[0012] By adopting the above technical solution and using multiple metal binders, the problem of easy softening of a single metal binder under high temperature conditions can be reduced. Furthermore, by combining multiple metal binders, the bonding force between the metal binder and cubic boron nitride is enhanced, thereby improving the hardness and wear resistance of the composite cutting tool and reducing wear.

[0013] Preferably, the organic binder is polyvinyl alcohol.

[0014] Preferably, the wear-resistant coating comprises the following raw materials in parts by weight: 5-8 parts titanium, 10-15 parts cobalt, and 5-10 parts nickel.

[0015] By adopting the above technical solution, using titanium, cobalt, and nickel metals as the main elements, a coating with high hardness and strong wear resistance is formed on the surface of the blade, thereby improving the wear resistance of the composite blade in high-temperature environments.

[0016] Preferably, the thickness of the wear-resistant coating is 0.01-2 μm.

[0017] By adopting the above technical solution, controlling the thickness of the wear-resistant coating within a reasonable range can promote the uniform and firm bonding of the wear-resistant coating components to the surface of the reinforcing layer, reducing the risk of incomplete bonding between the wear-resistant coating and the reinforcing layer due to excessive coating thickness, which would lead to excessive metal elements reducing the hardness and wear resistance of the composite blade.

[0018] Secondly, this application provides a method for preparing a heat-resistant and wear-resistant polycrystalline cubic boron nitride composite cutting tool, which adopts the following technical solution: A method for preparing a heat-resistant and wear-resistant polycrystalline cubic boron nitride composite cutting tool includes the following specific steps: Cubic boron nitride, ammonia and solvent are mixed in advance, and then tetraethyl orthosilicate is slowly added to react. The product is centrifuged, washed and dried, and a layer of nano-silica is coated on the surface of cubic boron nitride. Cubic boron nitride coated with silica, a binder, and an organic binder are mixed and sequentially ball-milled, dried, and pressed to obtain a base layer preform. Then, carbon nanotubes and carbon fibers are mixed and composited with the base layer preform to obtain a reinforcing layer preform. The reinforcing layer preform is then subjected to high-pressure and high-temperature sintering to obtain a preliminary cubic boron nitride composite cutting tool. Finally, a wear-resistant coating is obtained on the surface of the preliminary cubic boron nitride composite cutting tool by vapor deposition, thus obtaining a heat-resistant wear-resistant polycrystalline cubic boron nitride composite cutting tool.

[0019] By adopting the above technical solution, the composite blade with a multi-layer structure formed by combining various components improves the hardness, impact resistance and wear resistance of the blade, and reduces the wear phenomenon of the blade at high temperature.

[0020] Preferably, in the high-pressure high-temperature sintering, the temperature is 1000-1300℃, the high pressure is 4.5-7.0GPa, and the sintering time is 5-20min.

[0021] In summary, this application has the following beneficial effects: 1. This application improves the hardness and impact resistance of the cutting tool through a multi-layer structure. By coating the surface of cubic boron nitride with a dense layer of silicon dioxide, the impact toughness of the composite cutting tool is enhanced, reducing the problems of hardness decrease and breakage under high-temperature cutting. Simultaneously, the addition of reinforcing layers containing carbon nanotubes and carbon fibers, along with a wear-resistant coating, improves the wear resistance, strength, and thermal conductivity of the cutting tool, lowers the cutting temperature, reduces the temperature at which the tool hardness decreases at high temperatures, and enhances the high-temperature resistance and wear resistance of the composite cutting tool.

[0022] 2. In this application, the carbon fiber surface is hybridized to generate active oxygen-containing groups such as hydroxyl and carboxyl groups on the carbon fiber surface, which promotes the carbon fiber to have a large specific surface area and high activation, and uniformly and firmly bonded to the surface of cubic boron nitride, thereby improving the strength and impact resistance of the composite blade. Detailed Implementation

[0023] The present application will be further described in detail below with reference to the embodiments.

[0024] The average particle size of titanium powder, cobalt powder, and nickel powder is 50-100 nm.

[0025] The average particle size of titanium carbide and aluminum nitride is 50-100 nm.

[0026] The average particle size of cubic boron nitride is 5-10 μm.

[0027] Example of preparation of wear-resistant coating mixture Preparation Example 1 The wear-resistant coating mixture comprises the following raw materials in parts by weight: 7 kg titanium powder, 13 kg cobalt powder, and 8 kg nickel powder.

[0028] The preparation method of the wear-resistant coating mixture includes the following specific steps: Titanium powder, cobalt powder, and nickel powder are mixed evenly to form a wear-resistant coating mixture.

[0029] Preparation Example 2 The difference between Preparation Example 2 and Preparation Example 1 is that the amount of titanium powder used in the wear-resistant coating mixture is 5 kg, the amount of cobalt powder used is 15 kg, and the amount of nickel powder used is 5 kg.

[0030] Preparation Example 3 The difference between Preparation Example 3 and Preparation Example 1 is that the amount of titanium powder used in the wear-resistant coating mixture is 8 kg, the amount of cobalt powder used is 10 kg, and the amount of nickel powder used is 10 kg.

[0031] Example of preparation of base layer mixture Preparation Example 4 The base layer mixture comprises the following raw materials in parts by weight: 88 kg of cubic boron nitride, 15 kg of metallic binder, and 4 kg of organic binder. The metallic binder is a mixture of titanium carbide and aluminum nitride in a 1:1 mass ratio, and the organic binder is polyvinyl alcohol.

[0032] The preparation method of the base layer mixture includes the following specific steps: Cubic boron nitride and a metal binder are mixed and ball-milled at a ball-to-material ratio of 2:1 at a speed of 600 r / min for 4 hours. The mixture is then dried at 60°C, and an organic binder is added and mixed evenly. The mixture is then passed through a 100-mesh sieve to obtain the base layer mixture.

[0033] Preparation Example 5 The difference between Preparation Example 5 and Preparation Example 4 is that the surface of cubic boron nitride in the base layer mixture raw material is coated with a layer of nano-silica particles.

[0034] The preparation method of the base layer mixture includes the following specific steps: S1: Pre-place cubic boron nitride in anhydrous ethanol, add water, and the mass ratio of cubic boron nitride, anhydrous ethanol, and water is 2:5:2 to form a cubic boron nitride suspension. Then, add an appropriate amount of ammonia water to the cubic boron nitride suspension, and then slowly add tetraethyl orthosilicate and mix. The mass ratio of ammonia water, tetraethyl orthosilicate, and cubic boron nitride is 5:1.5:1.5. React for 5 hours, then centrifuge the product, wash it, and dry it, that is, coat the surface of cubic boron nitride with a layer of nano-silica.

[0035] S2: Mix the cubic boron nitride coated with nano-silica with a metal binder, and ball mill it at a ball-to-material ratio of 2:1 and a rotation speed of 600 r / min for 4 hours. Then dry it at 60℃, add an organic binder, mix it evenly, and pass it through a 100-mesh sieve to obtain the base layer mixture.

[0036] Preparation Example 6 The difference between Preparation Example 6 and Preparation Example 5 is that the amount of cubic boron nitride used in the base layer mixture raw material is 80 kg, the amount of metal binder is 20 kg, and the amount of organic binder is 3 kg.

[0037] Preparation Example 7 The difference between Preparation Example 7 and Preparation Example 5 is that the amount of cubic boron nitride used in the base layer mixture raw material is 95 kg, the amount of metal binder is 10 kg, and the amount of organic binder is 5 kg.

[0038] Example of preparation of reinforcing layer mixture Preparation Example 8 The reinforcing layer mixture comprises the following raw materials in parts by weight: 15 kg of carbon nanotubes and 8 kg of carbon fiber.

[0039] The preparation method of the reinforcing layer mixture includes the following specific steps: Carbon nanotubes and carbon fibers are mixed evenly to obtain a reinforcing layer mixture.

[0040] Preparation Example 9 The difference between Preparation Example 9 and Preparation Example 8 is that the amount of carbon nanotubes used in the reinforcing layer mixture is 10 kg, and the amount of carbon fiber used is 10 kg.

[0041] Preparation Example 10 The difference between Preparation Example 10 and Preparation Example 8 is that the amount of carbon nanotubes used in the reinforcing layer mixture is 20 kg, and the amount of carbon fiber used is 5 kg.

[0042] Preparation Example 11 The difference between Preparation Example 11 and Preparation Example 8 is that the carbon fiber surface in the reinforcing layer mixture raw material is hybridized.

[0043] The preparation method of the reinforcing layer mixture includes the following specific steps: Carbon fibers were first immersed in concentrated nitric acid for oxidation (liquid ratio 20:1), washed, and dried. Then, the oxidized carbon fibers were immersed in a mixed solution of maleic anhydride, ethyl acetate, and concentrated hydrochloric acid (liquid ratio 20:1, mass ratio of maleic anhydride, ethyl acetate, and concentrated hydrochloric acid 1:1:0.2) and heated to 60°C for 1 hour. The carbon fibers were then removed, washed, and dried. Finally, the carbon fibers were immersed in a urea-ethanol solution (liquid ratio 20:1, mass ratio of urea and ethanol 1:1) and heated to 70°C for 1 hour. The carbon fibers were then removed, washed, and dried to obtain surface-hybridized carbon fibers. Example

[0044] Example 1 This embodiment provides a heat-resistant and wear-resistant polycrystalline cubic boron nitride composite cutting tool, including a base layer, a reinforcing layer, and a wear-resistant coating. The reinforcing layer is located between the base layer and the wear-resistant coating. The raw material of the base layer is from Preparation Example 5, the raw material of the wear-resistant coating is from Preparation Example 1, and the raw material of the reinforcing layer is from Preparation Example 8.

[0045] The preparation method of heat-resistant and wear-resistant polycrystalline cubic boron nitride composite cutting tools includes the following specific steps: The base layer mixture is pressed into shape using a mold and pre-pressed at 11 MPa for 4 minutes to obtain a base layer blank. The reinforcing layer mixture is then coated onto the surface of the base layer blank, and the pressing continues for 5 minutes to obtain a reinforcing layer blank. Then, high temperature and high pressure sintering is performed at 1200℃ and 6 GPa for 8 minutes to obtain a cubic boron nitride composite cutting tool prototype. A wear-resistant coating mixture is then deposited on the surface of the cubic boron nitride composite cutting tool prototype by physical vapor deposition for 4 hours to form a wear-resistant coating with a thickness of 0.01-2 μm, thus obtaining a heat-resistant wear-resistant polycrystalline cubic boron nitride composite cutting tool.

[0046] Example 2 The difference between Example 2 and Example 1 is that the base layer material in the heat-resistant wear-resistant polycrystalline cubic boron nitride composite blade is derived from Preparation Example 5, the wear-resistant coating material is derived from Preparation Example 2, and the reinforcing layer material is derived from Preparation Example 8.

[0047] Example 3 The difference between Example 3 and Example 1 is that the base layer material in the heat-resistant wear-resistant polycrystalline cubic boron nitride composite blade is derived from Preparation Example 5, the wear-resistant coating material is derived from Preparation Example 3, and the reinforcing layer material is derived from Preparation Example 8.

[0048] Example 4 The difference between Example 4 and Example 1 is that the base layer material in the heat-resistant and wear-resistant polycrystalline cubic boron nitride composite blade is derived from Preparation Example 6, the wear-resistant coating material is derived from Preparation Example 1, and the reinforcing layer material is derived from Preparation Example 8.

[0049] Example 5 The difference between Example 5 and Example 1 is that the base layer material in the heat-resistant and wear-resistant polycrystalline cubic boron nitride composite blade is derived from Preparation Example 7, the wear-resistant coating material is derived from Preparation Example 1, and the reinforcing layer material is derived from Preparation Example 8.

[0050] Example 6 The difference between Example 6 and Example 1 is that the base layer material in the heat-resistant and wear-resistant polycrystalline cubic boron nitride composite blade is derived from Preparation Example 5, the wear-resistant coating material is derived from Preparation Example 1, and the reinforcing layer material is derived from Preparation Example 9.

[0051] Example 7 The difference between Example 7 and Example 1 is that the base layer material in the heat-resistant wear-resistant polycrystalline cubic boron nitride composite blade is derived from Preparation Example 5, the wear-resistant coating material is derived from Preparation Example 1, and the reinforcing layer material is derived from Preparation Example 10.

[0052] Example 8 The difference between Example 8 and Example 1 is that the base layer material in the heat-resistant and wear-resistant polycrystalline cubic boron nitride composite blade is derived from Preparation Example 5, the wear-resistant coating material is derived from Preparation Example 1, and the reinforcing layer material is derived from Preparation Example 11.

[0053] Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the base layer material in the heat-resistant wear-resistant polycrystalline cubic boron nitride composite blade is derived from Preparation Example 4.

[0054] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that no reinforcing layer is used in the heat-resistant wear-resistant polycrystalline cubic boron nitride composite blade.

[0055] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that no reinforcing layer and wear-resistant coating are used in the heat-resistant wear-resistant polycrystalline cubic boron nitride composite cutting tool.

[0056] Performance testing The heat-resistant wear-resistant polycrystalline cubic boron nitride composite cutting tools provided in Examples 1-8 and Comparative Examples 1-3 of this application were subjected to the following performance tests, and the specific test results are shown in Table 1.

[0057] Detection methods I. Hardness The microhardness of the composite blade prepared in this application was tested using an HX-1000TM / LCD microhardness tester. The test force was 9.807 N, and the test force holding time was 15 s.

[0058] II. Wear resistance The test was conducted on a high-speed, high-temperature friction and wear testing machine MG.2000. The friction pair was a ring-disc contact. The surface of the composite blade prepared in this application was subjected to a friction and wear test for 60 minutes under the conditions of 300N and 500℃. The friction coefficient of the composite blade after 60 minutes was recorded.

[0059] III. Bending Strength The bending strength of the composite blade prepared in this application was tested using the three-point bending method with a sample size of 4.5 mm radius and 0.8 mm thickness at room temperature, under test conditions of 7 mm span of the bending clamp and 1.5 mm diameter of the pressure roller.

[0060] Table 1: Performance Test Data Table Example 1 13.4 0.11 670 Example 2 13.1 0.12 660 Example 3 13.2 0.09 665 Example 4 13.3 0.12 668 Example 5 13.5 0.10 672 Example 6 13.2 0.11 663 Example 7 13.6 0.08 676 Example 8 14.6 0.06 705 Comparative Example 1 10.3 0.15 623 Comparative Example 2 8.5 0.17 605 Comparative Example 3 6.5 0.23 590 Performance testing results show that the cubic boron nitride composite cutting tool prepared in this application exhibits good strength and wear resistance, and can reduce wear of the composite cutting tool at high temperatures. This application improves the hardness and wear resistance of the composite cutting tool through a multi-layered structure. Simultaneously, a dense layer of nano-silica is coated on the surface of the cubic boron nitride, further enhancing the strength and toughness of the composite cutting tool.

[0061] In Example 8, the surface of the carbon fiber was modified by hybridization. The performance test results showed that the strength, wear resistance and toughness of the composite blade were further improved. This further illustrates that the surface hybridization modification of carbon fiber can promote better bonding between the reinforcing layer mixture and the base layer, thereby improving the strength and wear resistance of the composite blade.

[0062] A comparison between Comparative Example 1 and Example 1 shows that in Comparative Example 1, the surface of cubic boron nitride is not coated with silicon dioxide, and the hardness and wear resistance of the composite cutting tool will decrease significantly. This further demonstrates that the present application can coat the surface of cubic boron nitride with a dense silicon dioxide protective film, thereby improving the toughness and strength of the composite cutting tool.

[0063] A comparison of Comparative Examples 2 and 3 with Example 1 shows that the composite cutting tools prepared by Comparative Example 2 without a reinforcing layer and Comparative Example 3 without a wear-resistant coating and a reinforcing layer both exhibit reduced overall performance. This further demonstrates that the conventional single cubic boron nitride structure has limited hardness and wear resistance, and is prone to wear when exposed to high temperatures during cutting.

[0064] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A heat-resistant and wear-resistant polycrystalline cubic boron nitride composite blade, characterized in that, The material comprises a base layer, a reinforcing layer, and a wear-resistant coating. The reinforcing layer is located between the base layer and the wear-resistant coating. The base layer comprises the following raw materials in parts by weight: 80-95 parts cubic boron nitride, 10-20 parts metal binder, and 3-5 parts organic binder. The reinforcing layer comprises the following raw materials in parts by weight: 10-20 parts carbon nanotubes and 5-10 parts carbon fibers. The surface of the cubic boron nitride is coated with a layer of nano-silica particles. The carbon fibers are pre-modified with surface hybridization, and the surface hybridization modification method includes the following specific steps: Carbon fibers are first immersed in an acid solution for oxidation, then dried. The carbon fibers are then immersed in a mixture of concentrated hydrochloric acid and maleic anhydride, heated to react, then washed and dried. Finally, they are immersed in a urea solution and heated to react. The carbon fibers are then removed, washed, and dried to obtain surface-hybridized carbon fibers. The metal binder is at least two of titanium carbide, aluminum nitride, silicon nitride, and tungsten carbide, and the organic binder is polyvinyl alcohol.

2. The heat-resistant wear-resistant polycrystalline cubic boron nitride composite blade according to claim 1, characterized in that: The heating reaction temperature in the carbon fiber surface hybridization step is 60-70℃.

3. The heat-resistant wear-resistant polycrystalline cubic boron nitride composite cutting tool according to claim 1, characterized in that: The wear-resistant coating comprises the following raw materials in parts by weight: 5-8 parts titanium, 10-15 parts cobalt, and 5-10 parts nickel.

4. The heat-resistant wear-resistant polycrystalline cubic boron nitride composite cutting tool according to claim 1, characterized in that: The wear-resistant coating has a thickness of 0.01-2 μm.

5. A method for preparing a heat-resistant wear-resistant polycrystalline cubic boron nitride composite cutting tool as described in any one of claims 1-4, characterized in that: The specific steps include the following: Cubic boron nitride, ammonia and solvent are mixed in advance, and then tetraethyl orthosilicate is slowly added to react. The product is centrifuged, washed and dried, and a layer of nano-silica is coated on the surface of cubic boron nitride. Cubic boron nitride coated with silica, a binder, and an organic binder are mixed and sequentially ball-milled, dried, and pressed to obtain a base layer preform. Then, carbon nanotubes and carbon fibers are mixed and composited with the base layer preform to obtain a reinforcing layer preform. The reinforcing layer preform is then subjected to high-pressure and high-temperature sintering to obtain a preliminary cubic boron nitride composite cutting tool. Finally, a wear-resistant coating is obtained on the surface of the preliminary cubic boron nitride composite cutting tool by vapor deposition, thus obtaining a heat-resistant wear-resistant polycrystalline cubic boron nitride composite cutting tool.

6. The method for preparing the heat-resistant wear-resistant polycrystalline cubic boron nitride composite blade according to claim 5, characterized in that: In the high-pressure, high-temperature sintering process, the temperature is 1000-1300℃, the pressure is 4.5-7.0GPa, and the sintering time is 5-20 minutes.

Citation Information

Patent Citations

  • Removing metal from composite bodies and resulting products

    CA2099582A1

  • Grinding stamp mill

    CN105536968A